Influence of Direct and Indirect Domestic Violence on Dating Violence Victimization - You, Sukkyung (Journal of interpersonal violence, 2023)
This study investigated the relationship between domestic violence and dating violence victimization, and the mediating influence of the justification of dating violence among female Korean university students. The present study uses a cross-sectional survey (N = 550) to examine three research questions. First, does exposure to domestic violence during childhood predict dating violence victimization later in life? Second, does justifying violence mediate the relationship between domestic violence experience and dating violence victimization? Third, does justifying violence show a difference depending on the sexes of the perpetrator in influencing victimization of violence? A series of structural equation modeling analyses were conducted. The results showed that witnessing interparental violence and experiencing child abuse directly influenced dating violence victimization. Second, the justification of violence mediated the relationship between witnessing interparental violence and dating violence victimization. Third, justifying male to female violence influenced dating violence victimization. The study’s findings emphasize the importance of the gender-specific justification of violence among young female adults. This study makes essential empirical and theoretical contributions. A more in-depth understanding of the justification of violence between their prior and present experiences of violence in different contexts would support victims to recover and prevent poly-victimization experiences. Significant implications for school counselors as well as practitioners are discussed.